การควบคุมความชื้นโดยการปรับอัตราการไหลของอากาศ สำหรับเครื่องปรับอากาศแบบอินเวอร์เตอร์: Humidity Control Using Air Volume Flow Rate Adjustment for Inverter Air-Conditioner - Rachapradit, Ninnart (Asian Health, Science and Technology Reports, 2011)
งานวิจัยนี้ทำการศึกษาโดยใช้การปรับอัตราการไหลอากาศของเครื่องปรับอากาศแบบอินเวอร์เตอร์เพื่อควบคุมความชื้นสัมพัทธ์ของห้อง โดยทำการทดลองในห้องทดลองที่ใช้เครื่องปรับอากาศแบบอินเวอร์เตอร์ขนาด 3.52 kW ในสองส่วนแรกได้ศึกษาผลที่กระทบต่ออุณหภูมิและความชื้นสัมพัทธ์ของห้องที่ใช้เครื่องปรับอากาศแบบอินเวอร์เตอร์ เมื่อมีการเปลี่ยนแปลงปริมาณของอัตราการไหลของอากาศและปริมาณความชื้นที่เข้าสู่ห้อง ในการทดลองจะปรับอัตราการไหลของอากาศที่เครื่องปรับอากาศ 3 ระดับคือ 6.32 m 3 /min 7.72 m 3 /min และ 9.13 m 3 /min ส่วนการปรับปริมาณความชื้นจะใช้การเพิ่มลดจำนวนเครื่องให้ความชื้น แต่ละการทดลองจะตั้งค่าอุณหภูมิการทำงานของเครื่องปรับอากาศแบบอินเวอร์เตอร์ไว้ที่ 25 o C อุณหภูมิของอากาศที่ทางเข้าคอนเดนเซอร์ให้อยู่ 32 o C ผลจากการทดลองพบว่าทั้งการปรับปริมาณของอัตราการไหลของอากาศและการเพิ่มลดความชื้นที่เข้าสู่ห้อง มีผลกับความชื้นสัมพัทธ์ของห้องปรับอากาศ ในส่วนสุดท้ายใช้การปรับอัตราการไหลของอากาศมาควบคุมค่าความชื้นสัมพัทธ์ของห้อง โดยใช้รูปแบบการควบคุมแบบย้อนกลับ ในการทดลองจะตั้งค่าอุณหภูมิการทำงานของเครื่องปรับอากาศแบบอินเวอร์เตอร์ไว้ที่25 o C อุณหภูมิของอากาศที่ทางเข้าคอนเดนเซอร์ให้อยู่ 32 o C และตั้งค่าการควบคุมความชื้นสัมพัทธ์ของห้องที่ 55% RH จากผลการทดลองพบว่าสามารถควบคุมความชื้นสัมพัทธ์ของห้องให้อยู่ในช่วง 55 2% RH แสดงให้เห็นว่าเครื่องปรับอากาศแบบอินเวอร์เตอร์หากมีประยุกต์ใช้งานโดยมีการเพิ่มการควบคุมอัตราการไหลของอากาศตามความชื้นสัมพัทธ์ของห้องร่วมกับระบบอนิ เวอร์เตอรต์ ามเดิมของผผู้ ลติ จะสามารถควบคุมความชนื้ ของหอ้ งไดต้ ามต้องการ This study controls air volume flow rate in order to control relative humidity in the inverter air-conditioned room. The experiment was conducted in a lab equipped with 3.52 kW inverter air - conditioner. The first two parts of the study investigates the impact of air volume flow rate adjustment and humidity level on the room temperature and room relative humidity. The air volume flow rate at the air-conditioner has been set at three levels; 6.32 m 3 /min 7.72 m 3 /min และ 9.13 m 3 /min. The humidity is adjusted by increasing and decreasing the number of humidifier. Set point temperature of the air-conditioner is set at 25 o C while the inlet air temperature at condenser is set at 32 o C. The results show that both air volume flow rate level and humidity level have impacts on the room relative humidity. The last part of the study uses adjustment of air volume flow rate to control room relative humidity. Feedback control is employed in the study. Set point temperature of the air-conditioner is set at 25 o C and the inlet air temperature at condenser is set at 32 o C. The relative humidity is controlled at 55% RH. From the study, relative humidity can be controlled within 55 2% RH range. The results suggest that for inverter air-conditioner, if the control of room relative humidity using air volume flow rate adjustment together with typical inverter system, room temperature and room relative humidity can be controlled at the same time